(1542) The Egyptian economy and the poor in the eighties-main features, and the identification of the poor الاقتصاد المصري والفقراء في الثمانينيات - السمات الرئيسية، وتحديد هوية الفقراء - korayem, karima (معهد التخطيط القومى, 2019)

(untitled)
The present economic structure in the eighties which we shall focus upon in our description is not outcome of one form of economic structure that developed over the years, with it’s up and down. But it is offspring of different structure transformation that moved the economy from one extreme in the fifties – private sector`s domination - to another extreme sixties public sector` domination- then trying to move it again to somewhere in between these extremes, where the public and private sectors may share the economic activities more or less equality. Thus, the first questions that we shall address in this study is: what are the main features of this economy in the eighties